Species concept of golden flower camellias in China - Yanlei Liu; Ningning Xue; Chao Xu; Yiheng Wang; Xiaona Huang; Ran Sun; Xueying Yang; Jin Zhang; Jiahui Sun; Shiliang Zhou (BMC Plant Biology)
Abstract Background Golden flower camellias are valued in China as oil crops, medicinal plants and beautiful ornamental species. Due to overexploitation, all species of golden flower camellias are seriously endangered and have been regarded as the "giant panda of the plant kingdom". Unfortunately, the evolutionary relationships among golden flower camellia species are poorly understood, leading to frequent misidentifications. Results In this paper, we report our understanding of golden flower camellia species according to the phylogenies based on sequences of the internal transcribed spacer (ITS) and the whole chloroplast genome (cpG). We sequenced 95 ITS fragments and determined 65 cpGs. Combined with cleaned sequences downloaded from GenBank, the ITS dataset comprised 931 sequences representing 160 camellia taxa, and the cpG dataset included 322 genomes from 140 camellia taxa. Phylogenies based on both datasets suggested extensive interspecific hybridization and chloroplast genome capture events. Genome duplication and incomplete concerted evolution did not significantly affect phylogenetic reconstruction used for species identification based on ITS sequences. Conclusions A total of 23 golden flower camellia species are currently recognized as occurring in China. The ITS sequences are sensitive enough to discriminate all the re-circumscribed species and the cpG data are useful for tracing their geographical origins. Compared to non-golden flower camellias, the golden flower camellias have much lower genetic diversity. Considering that there are very few populations and even very few individuals, the golden flower camellias should be strictly protected in situ and conserved in nurseries ex situ. Future research efforts should be devoted to documenting the origins of hybrid species, and ex situ conservation efforts should be made toward evaluation and expansion of genetic diversity coverage.